Síntese otimizada de mecanismo de quatro barras - Bezerra, Roberto de Araújo (1996)
This work presents a study of the optimized synthesis of four-bar mechanisms, using optimization methods. In the beginning of this work the mechanisms are treated brieﬂy, where it is given a greater attention to four-bar mechanisms. The four-bar mechanisms synthesis is presented giving the equations of the trajectory synthesis of the couple point, passing nearest of the nine given points. Some optimization techniques” are presented. The objective function which represents the problem is shown. The optimization problem is then solved through the construction of a subroutine which generates the objective function and this subroutine is coupled to the optimization program. At last, the program is used to solve some case tests, which results in conclusions concerning relevant aspects of this research work.